A prospective study of cerebral, frontal lobe, and temporal lobe volumes and neuropsychological performance in children with primary brain tumors treated with cranial radiation. Issue 1 (29th August 2016) - Agbahiwe, Harold; Rashid, Arif; Horska, Alena; Mahone, E. Mark; Lin, Doris; McNutt, Todd; Cohen, Kenneth; Redmond, Kristin; Wharam, Moody; Terezakis, Stephanie
Abstract : BACKGROUND: Cranial radiation therapy (RT) is an important component in the treatment of pediatric brain tumors. However, it can result in long‐term effects on the developing brain. This prospective study assessed the effects of cranial RT on cerebral, frontal lobe, and temporal lobe volumes and their correlation with higher cognitive functioning. METHODS: Ten pediatric patients with primary brain tumors treated with cranial RT and 14 age‐ and sex‐matched healthy children serving as controls were evaluated. Quantitative magnetic resonance imaging and neuropsychological assessments (language, memory, auditory and visual processing, and vocabulary) were performed at the baseline and 6, 15, and 27 months after RT. The effects of age, the time since RT, and the cerebral RT dose on brain volumes and neuropsychological performance were analyzed with linear mixed effects model analyses. RESULTS: Cerebral volume increased significantly with age in both groups ( P  = .01); this increase in volume was more pronounced in younger children. Vocabulary performance was found to be significantly associated with a greater cerebral volume ( P  = .05) and a lower RT dose ( P  = .003). No relation was observed between the RT dose and the cerebral volume. There was no difference in the corresponding neuropsychological tests between the 2 groups. CONCLUSIONS: This prospective study found significant relations among the RT dose, cerebral volumes, and rate of vocabulary development among children receiving RT. The results of this study provide further support for clinical trials aimed at reducing cranial RT doses in the pediatric population. Cancer 2017;161–168. © 2016 American Cancer Society. Abstract : The radiation therapy dose and the cerebral volumes significantly correlate with vocabulary development in children treated with cranial radiation therapy. This prospective study supports clinical trials aimed at reducing cranial radiation therapy doses.